5-Aminolevulinic acid activates the MdWRKY71-MdMADS1 module to enhance anthocyanin biosynthesis in apple - Liuzi Zhang; Huihui Tao; Jianting Zhang; Yuyan An; Liangju Wang (Molecular Horticulture)
Abstract 5-Aminolevulinic acid (ALA), as a natural plant growth regulator, is well known for promoting red fruit coloring by enhancing anthocyanin accumulation. However, the underlying mechanisms remain elusive. In this study, we firstly demonstrated that ALA upregulates gene expression of the transcription factor MdMADS1, which in turn directly binds to and activates transcription of the key anthocyanin biosynthetic genes, MdCHS and MdUFGT. Then, we identified a novel WRKY transcription factor, MdWRKY71, that interacts with MdMADS1. Through gene manipulation, we revealed that MdWRKY71 plays a pivotal role in ALA-induced anthocyanin accumulation, highlighting its regulatory significance in this process. Further investigation unveiled that MdWRKY71 not only activates MdMADS1 transcription but also enhances its transcriptional activation on its target genes, MdCHS and MdUFGT. Additionally, we discovered that MdWRKY71 independently binds to and activates the transcription of two other anthocyanin biosynthetic genes, MdANS and MdDFR. The protein–protein interaction between MdWRKY71 and MdMADS1 amplifies the transcriptional activation of these genes by MdWRKY71. These findings delineate a fine and complex regulatory framework where MdWRKY71 and MdMADS1 coordinately regulate anthocyanin biosynthesis in apples, providing new insights into the molecular control of fruit coloration and offering potential target genes for breeding aimed at enhancing fruit quality.